Indicadores de concorrência, estrutura de mercado e globalizaç\~ao: Discuss\~ao conceitual e testes empíricos com dados Norte-Americanos - Glauco Avelino Sampaio Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The paper discusses the use of indicators, constructed with data from North American industrial sectors, and their application in the discussion of public policies, especially in competition policy, and to a lesser extent, in foreign trade policy. The premise is that the structure of domestic competition, manifested in concentration indices such as CR4 and HHI, affects the profit margin of economic sectors, reflecting in the markup, for example, prices in excess to costs (PCM), the variable to be explained. The higher concentration would lead to higher profits. Other indicators would have the ability to negatively affect the domestic profit margin, among which stands out the penetration of imports and the level of investment. The paper proposes a preliminary empirical exercise, based on recent literature that has been evaluating the increase in profits, sectoral concentration and globalization processes (investment, foreign trade) in the contemporary economy. The results lead to some empirical regularities, with some methodological limitations, such as the use of weak instruments. The fundamental objective is to indicate possible methodologies and discussions for replication in the Brazilian case.
Keywords: L1; L4; C26; F14; 330; competition indicators; market structure; competition policy; empirical tests; import